Supervisory Function in Controlling Single-Use Plastic Pollution in Makassar City - Andini Eka Putri; Sirajuddin Saleh; Jamaludin Jamaludin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study analyzed the supervisory function of the Environmental Agency of Makassar City in controlling environmental pollution caused by single-use plastic waste. Using a qualitative descriptive method, the research explored four key dimensions of supervision based on Terry’s control theory: standard setting, monitoring and evaluation, result comparison, and corrective actions. The findings showed that although the agency had a clear legal foundation through Mayor Regulation No. 21 of 2023 on the prohibition of plastic bags, operational standards and measurable performance indicators were not fully developed. Monitoring and evaluation were conducted only once a year, which limited the agency’s ability to capture variations in business compliance. The study also revealed that several business entities continued to violate the regulation, as evidenced by the issuance of warning letters. This indicated that the targets of plastic reduction had not been optimally achieved. Corrective actions remained limited to administrative warnings without structured follow-up mechanisms or tiered sanctions, which reduced their deterrent effect. Overall, the supervision function had been initiated but was not yet effective in ensuring consistent compliance and reducing single-use plastic waste. Strengthening operational standards, increasing monitoring frequency, improving data-based evaluation, and enforcing tiered sanctions were required to enhance environmental protection efforts in Makassar City.